Epigenetics Identifier screens reveal regulators of chromatin acylation and limited specificity of acylation antibodies - Kollenstart, Leonie; van der Horst, Sophie C.; Vreeken, Kees; Janssen, George M. C.; Martino, Fabrizio; Vlaming, Hanneke; van Veelen, Peter A.; van Leeuwen, Fred; van Attikum, Haico (Scientific reports, 2021)
The collection of known posttranslational modifications (PTMs) has expanded rapidly with the identification of various non-acetyl histone lysine acylations, such as crotonylation, succinylation and butyrylation, yet their regulation is still not fully understood. Through an unbiased chromatin immunoprecipitation (ChIP)-based approach called Epigenetics-IDentifier (Epi-ID), we aimed to identify regulators of crotonylation, succinylation and butyrylation in thousands of yeast mutants simultaneously. However, highly correlative results led us to further investigate the specificity of the pan-K-acyl antibodies used in our Epi-ID studies. This revealed cross-reactivity and lack of specificity of pan-K-acyl antibodies in various assays. Our findings suggest that the antibodies might recognize histone acetylation in vivo, in addition to histone acylation, due to the vast overabundance of acetylation compared to other acylation modifications in cells. Consequently, our Epi-ID screen mostly identified factors affecting histone acetylation, including known (e.g. GCN5, HDA1 , and HDA2 ) and unanticipated ( MET7 , MTF1, CLB3, and RAD26 ) factors , expanding the repertoire of acetylation regulators. Antibody-independent follow-up experiments on the Gcn5-Ada2-Ada3 (ADA) complex revealed that, in addition to acetylation and crotonylation, ADA has the ability to butyrylate histones. Thus, our Epi-ID screens revealed limits of using pan-K-acyl antibodies in epigenetics research, expanded the repertoire of regulators of histone acetylation, and attributed butyrylation activity to the ADA complex.